Programmable biomaterials for bone regeneration - Peiran Song; Dongyang Zhou; Fuxiao Wang; Guangfeng Li; Long Bai; Jiacan Su (Materials Today Bio)
Programmable biomaterials are distinguished by their ability to adjust properties and functions on demand, in a periodic, reversible, or sequential manner. This contrasts with traditional biomaterials, which undergo irreversible, uncontrolled changes. This review synthesizes key advances in programmable biomaterials, examining their design principles, functionalities and applications in bone regeneration. It charts the transition from traditional to programmable biomaterials, emphasizing their enhanced precision, safety and control, which are critical from clinical and biosafety standpoints. We then classify programmable biomaterials into six types: dynamic nucleic acid-based biomaterials, electrically responsive biomaterials, bioactive scaffolds with programmable properties, nanomaterials for targeted bone regeneration, surface-engineered implants for sequential regeneration and stimuli-responsive release materials. Each category is analyzed for its structural properties and its impact on bone tissue engineering. Finally, the review further concludes by highlighting the challenges faced by programmable biomaterials and suggests integrating artificial intelligence and precision medicine to enhance their application in bone regeneration and other biomedical fields.